SCAFFOLDING PROVIDED BY A TEACHER IN TEACHING WRITING NEWS ITEM TEXT - Mayang Sari Nirmala Dewi (Journal of English and Education, 2013)
This paper presents the outcome of qualitative research which particularly is aimed at investigating types of scaffolding, ways a teacher provides scaffolding, and benefits and challenges of scaffolding in teaching writing News Item text to tenth graders in a senior high school in Bandung, West Java. The data were obtained from non-participant classroom observation, field notes, and semi-structured interviews.  The results revealed that seven types of scaffolding were provided by the teacher.  The most intensive scaffolding was given in the Modeling stage of the curriculum cycle, and it was removed in the Independent Writing stage.  The results also show that the teacher faced some benefits and challenges in providing scaffolding. Keywords: Scaffolding, Teaching Writing, News Item text, Senior High School